For improvements in chromatic scales and luminescent fluxes of white lights: developing a dual-layer remote phosphor structure - Van Liem Bui; Nguyen Thi Phuong Loan; Hai Minh Nguyen Tran (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2023)
This study compares red-phosphor LaOF:Eu3+ impacts on a single-film remote phosphor configuration (SRPC) and a double-film remote phosphor configuration (DRPC). Mie theory is used to demonstrate the relationship between light flux and color quality. SRPC is a phosphor layer consisting of LaOF:Eu3+ particles mixed with YAG:Ce3+. Meanwhile, DRPC is two separate films of red and yellow phosphors. To increase scattering properties, we added 5% SiO2 into phosphor layers. The differences in structure affect significantly white light emitting diodes’ (WLEDs’) optical properties. Attained figures and statistics show that the color rendering indices (CRIs) increase along with the concentrations of both structures, and these numbers are approximately similar. However, DPRC exhibits a color quality scale (CQS) of 74 in all examined chromatic temperatures (5600 K - 8500 K), which is greater than SRPC’s 71 at 8500 K. Besides, the luminous efficiencies (LEs) in DRPC are more outstanding than that of SRPC, at given LaOF:Eu3+ concentration percentages (2%-14%). To summarize, DRPC offers greater benefits in luminous flux and color quality, compared to SRPC. Choosing the proper red light phosphor concentration, on the other hand, becomes a crucial aspect of achieving the ideal CQS and LEs.